Performance of diagnostic tests for Trypanosoma brucei brucei in experimentally infected pigs. - Kadidiata Ilboudo; Alain Boulangé; Robert Eustache Hounyèmè; Geoffrey Gimonneau; Jacques Kaboré; Adrien Gaston Marie Belem; Marc Desquesnes; Veerle Lejon; Mathurin Koffi; Vincent Jamonneau; Sophie Thévenon (Public Library of Science (PLoS), 2023)
Animal African trypanosomosis is an important vector-borne disease of livestock in sub-Saharan Africa. Pigs seem relatively tolerant to trypanosome infection and could act as a reservoir of trypanosomes affecting animals and humans. Our ability to reliably detect trypanosome infection in pigs depends on the performance of diagnostic tools, which is not well known. In pigs experimentally infected with Trypanosoma brucei brucei, we evaluated the performance of parasitological Buffy Coat Technique (BCT), two molecular (TBR and 5.8S PCR) and four serological tests (CATT, HAT Sero-K-Set rapid diagnostic test-RDT, indirect ELISA, immune trypanolysis). Most diagnostic tests showed high specificity, estimated at 100% (95% CI = 74-100%) with the exception of CATT and RDT whose specificity varied between 100% (95% CI = 74-100%) to 50% (95% CI = 7-93%) during the experiment. The sensitivity of each test fluctuated over the course of the infection. The percentage of positive BCT over the infection (30%) was lower than of positive PCR (56% and 62%, depending on primers). Among the serological tests, the percentage of positive tests was 97%, 96%, 86% and 84% for RDT, ELISA, immune trypanolysis and CATT, respectively. Fair agreement was observed between both molecular tests (κ = 0.36). Among the serological tests, the agreement between the ELISA and the RDT was substantial (κ = 0.65). Our results on the T.b. brucei infection model suggest that serological techniques are efficient in detecting the chronic phase of infection, PCR is able to detect positive samples several months after parasites inoculation while BCT becomes negative. BCT examination and RDT are useful to get a quick information in the field, and BCT can be used for treatment decision. ELISA appears most suited for epidemiological studies. The selection of diagnostic tests for trypanosomosis in pigs depends on the context, the objectives and the available resources.